If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 4 + -1x + 6 = 4 Reorder the terms: 4 + 6 + -1x + -1x = 4 Combine like terms: 4 + 6 = 10 10 + -1x + -1x = 4 Combine like terms: -1x + -1x = -2x 10 + -2x = 4 Solving 10 + -2x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -2x = 4 + -10 Combine like terms: 10 + -10 = 0 0 + -2x = 4 + -10 -2x = 4 + -10 Combine like terms: 4 + -10 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| -4m+3=24 | | 6=(-3x)+6 | | 66=6(8x-4)-6(x+6) | | C=50m+250 | | 2c^2+15c+18= | | X/10-5=-4 | | 2.5x-8=13-4.5 | | 24-6x=6(x-5)-6 | | 2/b-4 | | Y/4/5=20 | | 12x+12+12x=90 | | c^2+35c=0 | | -1-6x=9-2 | | 3n-5=/ | | 9t+4=-14E | | 12r^2+7rs-10s^2= | | 1-2/3x=-15 | | 3(k-8)-(k+5)=23 | | -20x^2+180=0 | | 5-x=9x+5 | | (3z+5)(z+3)=7 | | 12+4c=6-(19+13) | | 1=2/3=-15 | | 12+12x+12x=90 | | 5+(n+3)+4n= | | 2x^2-11x+17=0 | | y=-2(8)+7 | | 6x-8=-6 | | -7x-9+6x=-15 | | -7x-9+6x=-15 | | 3/8y=3 | | (-4x^4/3x^7)^-2 |